Recollection of Lysionotus kingii (C.B.Clarke) Hilliard (Gesneriaceae) after 138 years, and its expanded description - Sherpa, N.; Mangar, S.; Chettri, B.; Chhetri, G.; Franklin Benjamin, J. H.; Gogoi, R. (Rheedea, 2025)
Lysionotus kingii (C.B.Clarke) Hilliard (Gesneriaceae) is recollected after a gap of 138 years. A detailed description of L. kingii and information on its identity is provided here.